New Improved Nonsingular Fast Terminal Sliding Mode Control (NFTSMC) for Current Control of Three Phase Induction Motor - Ashraf Hagras; Ahmed Elkousy (JES: Journal of Engineering Sciences)
This paper proposes new improved Nonsingular Fast Terminal Sliding Mode Control (NFTSMC) technique for current control of Three Phase Induction Motor (TPIM). This technique adds more advantages to the conventional terminal sliding mode control theory to speed and smooth the torque and speed response under varying conditions. The proposed new improved nonsingular fast terminal sliding mode control technique overcomes the traditional demerits of Terminal Sliding Mode Control (TSMC) theory like the limited values of its constraints and its state differentiation and avoids the complexity of its following versions. This supports the simplicity of controller design and its easy adaptability to achieve its targets. The stability of the proposed method was analyzed and guaranteed using Lypunov stability theory. Therefore, this technique was compared with nonlinear hysteresis controller using MATLAB/SIMULINK to validate its design and show its faster starting torque, speed response, with small torque effect at step load change compared to the hysteresis controller and for constant flux operation at different inertia. Besides that, it offers strong robust performance against electrical, mechanical parameters uncertainties and external load disturbances.